2022
DOI: 10.1155/2022/9682032
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Metabolic Syndrome Components and COVID-19 Disease Severity in Hospitalized Patients: A Pilot Study

Abstract: Background. Preliminary data suggest that patients with comorbidities are more susceptible to severe COVID-19 infection. However, data regarding the presence of metabolic syndrome (MetS) in patients with COVID-19 are scarce. Aim. In the present study, we aim to investigate the association between MetS components and disease severity in hospitalized COVID-19 patients. Methods. We conducted a prospective observational study of 90 hospitalized patients with COVID-19 pneumonia at a tertiary hospital. The study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Ferritin is another biomarker that has been associated with severity in adults and is able to predict poor outcomes and prognosis, although its use is still somewhat contested [ 47 , 48 , 49 ]. In our patients, ferritin proved to be a good predictor of severity, ICU admission and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin is another biomarker that has been associated with severity in adults and is able to predict poor outcomes and prognosis, although its use is still somewhat contested [ 47 , 48 , 49 ]. In our patients, ferritin proved to be a good predictor of severity, ICU admission and death.…”
Section: Discussionmentioning
confidence: 99%
“…HDL cholesterol has been associated with poorer outcomes and more severe cases [ 21 , 50 ]. It has been suggested that it is involved in the regulation of innate immune response through interaction with ABCA1 or ABCG1, which negatively regulates T-cell activation and the expression of inflammatory mediators [ 49 ]. In our study, HDL correlated inversely with severity, ICU admission and death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the exploration of HDL-c levels in pediatric COVID-19 patients by Mietus-Snyder et al 28 , and its significant reduction in severe cases as reported by Agouridis et al 29 and Erman et al 30 , extends the relevance of HDL-c as a prognostic factor across age groups. The examination of lipid ratios, such as those undertaken by Rohani-Rasaf et al 31 and Alcántara-Alonso et al 32 , further elucidates the role of lipid profiles in predicting COVID-19 outcomes, with Zhang et al 24 emphasizing the TG/HDL-c ratio as a marker of cardiovascular risk and poor prognosis in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 84%
“…Xiuqi y col. (Wei et al, 2020) en su estudio reportaron que los niveles de LDL-c y TC fueron significativamente más bajos en pacientes con COVID-19 en comparación con sujetos normales (P < 0,001) donde hubo disminuciones significativas y graduales en los niveles de LDL-c (mediana (IQR) en mg/dL, leve: 91 (76, 104); grave: 86 (69, 102); crítico: 69 (48, 81); P < 0,02) y CT (leve: 173 (148,203);grave: 167 (138,197); crítico: 125 (95, 162); P < 0,05) en los tres grupos. Resultados que confirman lo reportado por Erman et al (Erman et al, 2022) en donde los niveles sericos de triglicéridos (p=0,007) fueron significativamente mayores en pacientes con enfermedad grave por COVID-19.…”
Section: Discussionunclassified